Application of BioTranspezia Multimedia to the Learning Outcomes Students of SMA Muhammadiyah 1 Surakarta - Ima Aryani; Auranur Priyanka Rahim (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2025)
BioTranspezia is a multimedia that is useful for improving student’s understanding so that it has an impact on their learning results. This study was carried out because learning media that is still often found is less interesting so that learning tends to be boring. This study aims to see the impact of the application of BioTranspezia multimedia on the learning outcomes of high school students in learning Biology of Transport and Human Body Substance Exchange. The method in this study is quantitative using a type of Pre-experimental research with a One Group Pretest-Posttest Design. The instruments used are in the form of question sheets (Pretest-Posttest) and affective observation sheets. Statistical data analysis uses normality tests, homogeneity tests, also hypothesis tests. The results showed that there was a significant difference in cognitive learning outcomes in the average Pretest as well as Posttest scores, namely the Pretest of 65 and the Posttest of 80,69. Likewise, in the achievement of the affective aspect, there was an increase in each indicator in the second meeting consisting of a discipline indicator of 74,30%, a cooperation indicator of 73,61%, a responsibility indicator of 76,38%, and an activeness indicator of 70,13% with the four indicators included in the good category. Thus in this research, it can be concluded that the implementation of BioTranspezia multimedia has an effect on student learning outcomes at SMA Muhammadiyah 1 Surakarta in learning Biology.